2021
DOI: 10.1186/s40733-021-00079-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of monitoring personal air pollution exposure with sensors for asthma self-management

Abstract: Background Exposure to fine particulate matter (PM2.5) increases the risk of asthma exacerbations, and thus, monitoring personal exposure to PM2.5 may aid in disease self-management. Low-cost, portable air pollution sensors offer a convenient way to measure personal pollution exposure directly and may improve personalized monitoring compared with traditional methods that rely on stationary monitoring stations. We aimed to understand whether adults with asthma would be willing to use personal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In China and the United States, Air beam units were used for spatial modeling of particulate matter air pollution sensor measurements collected by community scientists while cycling, land use regression with spatial cross-validation, and applications of machine learning for data correction; feasibility and acceptability of monitoring personal air pollution exposure with sensors for asthma self-management (Adams et al, 2020; Guevara-Luna et al, 2020; Xie et al, 2021). Although air sensors are not a replacement for regulatory monitors, they entail a valuable teaching tool (Anastasiou et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In China and the United States, Air beam units were used for spatial modeling of particulate matter air pollution sensor measurements collected by community scientists while cycling, land use regression with spatial cross-validation, and applications of machine learning for data correction; feasibility and acceptability of monitoring personal air pollution exposure with sensors for asthma self-management (Adams et al, 2020; Guevara-Luna et al, 2020; Xie et al, 2021). Although air sensors are not a replacement for regulatory monitors, they entail a valuable teaching tool (Anastasiou et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…(2021) simultaneously obtained PM measurements from personal monitors and regulatory monitors to study exposures in individuals with asthma, and demonstrated that the portable monitors were better able to capture personalized air quality information compared to the traditional method. 37 However, despite these advantages, the wide use of personal monitors for exposure studies is limited for several reasons. Personal monitors and methods that have been validated and are of research grade have been expensive and require initial training to use, particularly for monitoring of gases and volatile organic compounds (VOCs).…”
Section: Gaps In Monitoring Methods and Technological Limitationsmentioning
confidence: 99%
“…For example, although none of the studies in this Special Issue employed personal exposure monitors, research using such devices suggests exposure biomarkers vary by individual (Liang et al., 2019 ). Indeed, technologies are being marketed commercially and conducting research using individual‐exposure measurement approaches may soon be more cost‐effective, feasible, and acceptable (Caplin et al., 2019 ; Steinle et al., 2013 ; Xie et al., 2021 ).…”
Section: Creative Sophisticated and Rigorous Methodsmentioning
confidence: 99%